H.M.'s contributions to neuroscience: A review and autopsy studies. Issue 11 (23rd September 2014) - Augustinack, Jean C.; van der Kouwe, André J.W.; Salat, David H.; Benner, Thomas; Stevens, Allison A.; Annese, Jacopo; Fischl, Bruce; Frosch, Matthew P.; Corkin, Suzanne
ABSTRACT H.M., Henry Molaison, was one of the world's most famous amnesic patients. His amnesia was caused by an experimental brain operation, bilateral medial temporal lobe resection, carried out in 1953 to relieve intractable epilepsy. He died on December 2, 2008, and that night we conducted a wide variety of in situ MRI scans in a 3 T scanner at the Massachusetts General Hospital (Mass General) Athinoula A. Martinos Center for Biomedical Imaging. For the in situ experiments, we acquired a full set of standard clinical scans, 1 mm isotropic anatomical scans, and multiple averages of 440 μm isotropic anatomical scans. The next morning, H.M.'s body was transported to the Mass General Morgue for autopsy. The photographs taken at that time provided the first documentation of H.M.'s lesions in his physical brain. After tissue fixation, we obtained ex vivo structural data at ultra‐high resolution using 3 T and 7 T magnets. For the ex vivo acquisitions, the highest resolution images were 210 μm isotropic. Based on the MRI data, the anatomical areas removed during H.M.'s experimental operation were the medial temporopolar cortex, piriform cortex, virtually all of the entorhinal cortex, most of the perirhinal cortex and subiculum, the amygdala (except parts of the dorsal‐most nuclei—central and medial), anterior half of the hippocampus, and the dentate gyrus (posterior head and body). The posterior parahippocampal gyrus and medial temporal stem were partially damaged. Spared medial temporal lobe tissue included the dorsal‐most amygdala, the hippocampal‐amygdalo‐transition‐area, ∼2 cm of the tail of the hippocampus, a small part of perirhinal cortex, a small portion of medial hippocampal tissue, and ∼2 cm of posterior parahippocampal gyrus. H.M.'s impact on the field of memory has been remarkable, and his contributions to neuroscience continue with a unique dataset that includes in vivo, in situ, and ex vivo high‐resolution MRI. © 2014 Wiley Periodicals, Inc.